Skeletal scintigraphy indicates disease severity of cardiac involvement in patients with senile systemic amyloidosis - Kristen, Arnt; Haufe, Sabine; Schönland, Stefan; Hegenbart, Ute; Schnabel, Philipp Albert; Röcken, Christoph; Hardt, Stefan; Lohse, Peter; Ho, Anthony Dick; Haberkorn, Uwe; Dengler, Thomas; Altland, Klaus; et al. (International journal of cardiology, 2013)
Background - Senile systemic amyloidosis (SSA) is a common aging phenomenon in the elderly population. Nevertheless, pre-mortem diagnosis of SSA is rare. Thus, data on clinical characterization and disease severity are limited. - Methods - 36 consecutive SSA patients (71.6 [64.7-82.7]years) were evaluated by electrocardiography, echocardiography, laboratory tests, and 99mTechnetium-3,3-diphosphono-1,2-propanodicarboxylic acid (99mTc-DPD) scintigraphy (n=20). - Results - In addition to cardiac involvement, amyloid deposition was found in rectum (n=6), peripheral nerves (n=2), and urinary bladder (n=2). Five patients showed low voltage pattern. Thickness of interventricular septum (IVS) was 20 [12-27]mm. LV longitudinal function was diminished (TDI-s 5 [3-11] cm/s; MAPSE 6.5 [2.5-19]mm; TAPSE 12.5 [2-24]mm). LV systolic function (LV-EF<45%) was markedly decreased in 19 patients. Plasma levels of troponin T (0.05 [0.01-0.23]µg/L) and NT-proBNP (4318 [205-16597]ng/L) were elevated. 99mTc-DPD heart retention was 7.8 [2.4-11.0]% and correlated with MAPSE (ρ=−0.716; p=0.0018), TAPSE (ρ=−0.491; p<0.05), and IVS (ρ=0.556; p=0.0153). Heart-to-body ratio correlated with MAPSE (ρ=−0.771; p=0.0018), IVS (ρ=0.603; p=0.0086). Twelve patients died during follow-up of 27.4 [0.1-106.2]months. Exclusively 99mTc-DPD heart retention, diastolic dysfunction and in trend MAPSE were associated with patient's outcome. Interestingly, risk predictors that were well established in patients with AL amyloidosis were not predictive for survival in patients with SSA. - Conclusions - This study gave first evidence that 99mTc-DPD HR may be capable to display the extent of cardiac amyloid deposition. Moreover, this study suggested that 99mTc-DPD HR, diastolic dysfunction and in trend MAPSE are associated with poor outcome. Nevertheless, these findings need to be established in a larger prospective trial.
Available online 20 July 2011
Gesehen am 31.03.2021